A Cross-Sectional Study on the Association between Physical Activity and Cognitive Function Among Community-Dwelling Older Adults in Tianjin - Wang, Tianyu; Duan, Keran; Cai, Xian; Chen, Qi; Zu, Liping; Liu, Lingyan; Wu, Xiaomin; Li, Chenyu; Ma, Fei (Current Alzheimer Research, 2024)
BackgroundThe association between physical activity (PA) and cognitive function remains controversial, and the impact of gender on this association remains underexplored. Therefore, this study aimed to investigate the association between PA and cognitive function and to explore whether this association was modified by gender among older adults.MethodsIn 2016, a cluster sampling method was used to select community-dwelling older adults aged 65 and above. PA was assessed using the International Physical Activity Questionnaire-Short Form and classified as low, middle, and high. Cognitive function was assessed using the revised Chinese version of the Wechsler Adult Intelligence Scale. The multiple linear regression model was used to explore the association between PA and cognitive function and to assess whether this association differs by gender.ResultsA total of 676 participants with a mean age of 73.63 ± 6.39 were included. The multiple linear regression analysis showed that higher PA was significantly statistically associated with higher Full Intelligence Quotient (FIQ), Performance Intelligence Quotient (PIQ), and verbal Intelligence Quotient (VIQ) scores (P<0.05). Among the WAIS-RC subtests, higher PA was significantly statistically associated with higher scores of the similarity subtest, picture completion subtest, and picture arrangement subtest (P<0.05). In the gender subgroup analysis, higher PA was significantly statistically associated with higher FIQ and PIQ scores (P<0.05), but no significant association was found with VIQ scores (P>0.05) in the male group, while in the female group, there was no significant statistical association between higher PA and FIQ, PIQ, or VIQ scores (P>0.05).ConclusionHigher PA was significantly statistically associated with better cognitive function (P<0.05). In the male group, PA was significantly statistically associated with cognitive function, whereas no comparable association was found in the female group.
Keywords: PIQ